KONSTRUKSI CONTENT MEDIA MASSA DAN REMAJA MELEK POLITIK - Farida Farida (SEMIOTIKA: Jurnal Komunikasi, 2013)
Capitalism in the era of mass media content selection by media managers strongly influenced by the imagery that has been attached to the audience so that it feels need to change the image that has been attached to the audience. Of imaging the hedonistic, consumerist and not treat politic like a politically literate adolescent. Mass media is supposed to be the power of the state to promote the election. With the socializationsih of youth or first time voters are expected to gain knowledge as well as early political learning. How teens can finally understand what the election and the election itself what is the meaning for them, and how they can be on the poll.Keywords: mass media content, media management, imaging, voters,socialization